PENGEMBANGAN SISTEM INFORMASI ALUMNI BERBASIS WEB: STUDI KASUS PADA SMK NW TEMBENG PUTIK - Muhammad Anshori (Scientia Integritas Utama, 2022)
This study aims: (1) to develop a web-based alumni information system, (2) to determine the feasibility of a web-based alumni information system. The type of research used is Research and Development (R & D). This research is a type of development research using the waterfall method. There are four stages, namely (1) analysis, (2) design, (3) implementation, and (4) testing. This research was conducted at SMK NW Tembeng Putik. Product usability validation was carried out by two media experts and 20 user responses as well as system testing in this study using GTMetrix and WAPT. Methods of data collection is done by observation, interviews and questionnaires. The data analysis technique used is descriptive statistical analysis technique. The results of this study were obtained: (1) Produce a web-based alumni information system, the final product that has been developed is a web-based alumni information system and the ability of the system is to track the whereabouts and register alumni (2) assessment by media experts on the functionality aspect is 91 % in the category of Very Useful. In addition, the assessment of twenty respondents which includes students of SMK NW Tembeng Putik on the usability aspect is 96% so that it is in the Very Good category and on the performance test with GTMetrix is grade A from the results of page loading 0.86 seconds for the speed index, then assessment for the average performance is 96.5%.